Isolation and Quantification of Chemical Marker of Polygonatum verticillatum: First Report - Kaur Virk, Jaswinder; Bansal, Parveen; Kumar, Sanjiv; Singh, Ranjit; Kumar Rawal, Ravindra (Current Traditional Medicine, 2016)
Background: Polygonatum verticillatum (Mahameda) is an important ingredient of Ashtawarga and other costly Ayurvedic formulations. Nowadays, due to large scale and indiscriminate collection of wild material, it has come under the category of endangered plants. To overcome the scarcity, substitutes of Mahameda are being commonly used in market by manufacturers. These substitutes differ from authentic plant by Ayurvedic and pharmacologic theory of drug action that leads to lowered efficacy of the formulation along with high charging from consumers on pretext of using costly Ashtawarga plants in the formulation. Objective: To isolate and quantify the therapeutically active ingredients that can be used as marker for identification of unauthorized substitution. Methods: Methanolic extract of rhizomes of plant was subjected to preliminary phytochemical screening followed by column chromatography for isolation of marker/markers. Column was first eluted with pure hexane and polarity of solvent was gradually increased. Total 1180 fractions were collected and pooled on the basis of TLC profiling. The single compound was isolated and confirmed by chemical test, melting point, spectral analysis and compared with reference compound as well as literature. Quantification of isolated compound in the extract was done by HPTLC. Results: Phytochemical screening of extract shows the presence of flavonoids, carbohydrates, terpenoids, phenolics and alkaloids. A pure white crystalline powder characterized as 4- hydroxy-3-methoxy-cinnamic acid (Ferulic acid) was isolated by column chromatography. The yield of isolated ferulic acid was found to be 0.89 %. Conclusion: The isolated compound is the first report of presence of novel compound ferulic acid in this plant and can also be used as a marker for standardization.
Keywords: isolation